2013
DOI: 10.1016/j.apnu.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Effects of Gentle Hatha Yoga for Women With Major Depression: Findings From a Randomized Controlled Mixed-Methods Study

Abstract: Major depressive disorder (MDD) is a common, debilitating chronic condition in the United States and worldwide. Particularly in women, depressive symptoms are often accompanied by high levels of stress and ruminations, or repetitive self-critical negative thinking. There is a research and clinical imperative to evaluate complementary therapies that are acceptable and feasible for women with depression and that target specific aspects of depression in women, such as ruminations. To begin to address this need, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 69 publications
(89 reference statements)
7
101
1
1
Order By: Relevance
“…This explanation finds support in the context of previous findings highlighting the role of yoga in facilitating a sense of connectedness with oneself and others in a population of depressed women (Kinser et al, 2013;Uebelacker et al, 2010a) and may inform theories targeting self-efficacy as a mediator in the pathway between yoga and improved psychological and physical health (Uebelacker et al, 2010b).…”
Section: Secondary Outcomes Anxietysupporting
confidence: 48%
See 1 more Smart Citation
“…This explanation finds support in the context of previous findings highlighting the role of yoga in facilitating a sense of connectedness with oneself and others in a population of depressed women (Kinser et al, 2013;Uebelacker et al, 2010a) and may inform theories targeting self-efficacy as a mediator in the pathway between yoga and improved psychological and physical health (Uebelacker et al, 2010b).…”
Section: Secondary Outcomes Anxietysupporting
confidence: 48%
“…More recent feasibility and acceptability data from a yoga study on 27 depressed women suggested that work and personal responsibilities were key barriers to participating and completing the study. Yoga's acceptability was supported by improved mood and a feeling of connectedness amongst the participants and with other participants in the class (Kinser, Bourguignon, Whaley, Hauenstein, & Taylor, 2013). Taken together, investigation into yoga as a CAM therapy for improving and maintaining emotional and physical health is gaining momentum in the empirical literature (Field, 2011;Li & Goldsmith, 2012;Lin, Hu, Chang, Lin, & Tsauo, 2011;Ross et al, 2013).…”
Section: History Of Yogamentioning
confidence: 99%
“…Women with major depressive disorder who completed an 8-week Hatha Yoga intervention were shown to have lower levels of depressive symptoms, and ruminate less on negative events [18]. In preventing emotional states that cloud the points of one's attention, yoga may aid in alleviating depressive symptoms by channeling cognitive and emotional energies into productive states that are advantageous for subjective well-being.…”
Section: Body Mind Spirit Approachmentioning
confidence: 99%
“…First, it is a commonly practiced PA modality in the United States and is generally easily available through in-person classes or internetbased resources [52][53][54]. Second, my team's research suggests that pregnant women are explicitly expressed interest in yoga for symptom management [55][56][57]. We have recently completed focus groups with pregnant women and new mothers during which we learned that many women do not receive encouragement from their obstetricians to engage in PA [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, yoga provides an opportunity to be mindful of symptoms and adapt the practice according to those symptoms; for example, specific gentle breathing practices and movements may be advisable when one is experiencing predominantly depressive symptoms (e.g., lethargy, anhedonia) and others are more appropriate when anxious symptoms are predominant (e.g., ruminations) [50,56,70].…”
Section: Introductionmentioning
confidence: 99%